SEEKING ASYLUM IN THE MIDDLE EAST: Lessons from the Syrian crisis - Kaya, Ayhan (Taylor and Francis, 2022)
This chapter delves into the similarities and differences of political and societal discourses of reception, protection, and integration of Syrian refugees in Iraq, Jordan, Lebanon, and Turkey. The chapter aims to give a main understanding and perspective to the reader and point to further readings. The chapter will demonstrate that a religio-political discourse of reception based on guesthood and the Ansar spirit revitalising the practice of migration of Prophet Mohammad and his followers from Mekka to Medina was implemented in these countries during the first years of the Syrian mass migration. However, this discourse is no longer embraced by the majority of receiving societies in these countries. The chapter claims that the preliminary discourse of guesthood that is likely to place emphasis on temporariness has recently posed impediments before the integration and social cohesion of Syrian refugees. © 2023 selection and editorial matter, Anna Triandafyllidou; individual chapters, the contributors.